Does system think in climate change content needs formal operational?. Issue 2 (February 2019) - Meilinda, M; Rustaman, N Y; Firman, H; Tjasyono, B
Abstract: This research aims to know the impact of formal operational in system thinking skills on climate change content through climate change course which is using system approach epistemology. The research design is quasi experiment by comparing groups of students with formal pre-operational and operational on two lectures i.e. human and environment (n=34) and Earth and Space Science (n = 30). Testing the level of students reasoning are using reasoning test TOLT and CCSTI (Climate Change System Thinking Instrument) for testing student system thinking skills. The results showed that the level of students' reasoning on the lecture of the human and environment affect the system thinking skills especially Indicators III and IV indicators with a value of Cronbach alpha 0.048< 0.005 and 0.008<0.005 Meanwhile the level of reasoning has no effect on student teachers of physical education with the Cronbach alpha value of 0.005 >. Based on the value of Cronbach Alpha obtained, it can be concluded that it was not a formal knowledge which affects the system thinking skills in climate change content but the prerequisites knowledge and post formal operational.